Lines of credit and investment: Firm-level evidence of real effects of the financial crisis - Karolina Holmberg (Sveriges Riksbank, 2013)
Using Swedish bank lending data, investment data and accounting data, I examine how the financial crisis affected corporate investment through its effect on credit availability. Sensitivity to a credit supply shock is measured as credit reserves, defined as unused credit on lines of credit. I find that firms with low credit reserves reduced investment significantly more than other firms. However, it is not possible to determine that this relationship was caused by a shift in the supply of credit. Overall, I find no statistically strong evidence that the decline in investment was exacerbated by a contraction in credit supply.
Keywords: E22; E44; G01; G31; G32; 330; Corporate investment; Crisis; Financial Markets and the Macroeconomy; Lines of Credit